IMF Staff papers : Volume 11 No. 1. (IMF Staff Papers; IMF Staff Papers ;, 1964)
This paper focuses on official intervention on the forward exchange market. The purpose is to provide a straightforward account of the theory of intervention and to use it to discuss the problems raised. The forward exchange market may be conveniently treated in terms of stocks rather than of flows; that is, the forward exchange rate is taken as reconciling the desires of market participants with respect to the holding-rather than the changing-of forward exchange positions. Official intervention in the forward exchange market can be analysed by regarding the authorities either as part of the market or as distinct from it. Official swap transactions are frequently undertaken not on the open market but by direct arrangement with foreign monetary authorities or with commercial banks. The substantial rise to be expected in the forward premium would, of course, have an adverse effect on the foreign balance, which might be unwelcome from a cyclical standpoint though it would probably merely involve a diminution in the improvement that would otherwise have occurred as a result of the recession.